2014
DOI: 10.1371/journal.pone.0109316
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Drug Uptake during Mass Drug Administration for Control of Lymphatic Filariasis in Rural and Urban Tanzania

Abstract: BackgroundIn most countries of Sub-Saharan Africa, control of lymphatic filariasis (LF) is based on annual mass drug administration (MDA) with a combination of ivermectin and albendazole. Treatment coverages are however often suboptimal for programmes to reach the goal of transmission interruption within reasonable time. The present study aimed to identify predictors and barriers to individual drug uptake during MDA implementation by the National LF Elimination Programme in Tanzania.MethodsA questionnaire base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
56
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 25 publications
11
56
1
Order By: Relevance
“…In the current study, being absent during drug distribution was cited as the major reason for not taking the drugs. This was also noted in studies conducted previously in other parts of Tanzania (Kisoka et al, 2014, Simonsen et al, 2014). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the current study, being absent during drug distribution was cited as the major reason for not taking the drugs. This was also noted in studies conducted previously in other parts of Tanzania (Kisoka et al, 2014, Simonsen et al, 2014). …”
Section: Discussionsupporting
confidence: 87%
“…The surveyed percentages of drug uptake in the current study were lower than the minimum of 65% required to attain the interruption of LF transmission, and this observation has been documented in other places implementing the programme (World Health Organization, 2011). Lower than optimal drug uptake is a challenge to the success of MDA campaigns in some areas of Tanzania (Kisoka et al, 2014, Simonsen et al, 2014). In the current study, being absent during drug distribution was cited as the major reason for not taking the drugs.…”
Section: Discussionmentioning
confidence: 99%
“…(Rural setting)Lofa County, Kolahun District.To assess community leaders’knowledge and attitudes regarding resumption of MDA for NTDs after the Ebola virus disease epidemic (EVD).Shift in national health systems priorities regarding funding, research and development due to EVD.Temporally halt to all MDA for LF activities in EVD affected areas.Fears in the community that EVD and MDA might be linked, hence affecting compliance/coverageProgramme sustainability, community participation and coverage3. Kisoka et al, 2014 [21]/Tanzania/May and August 2011Cross sectional household surveyData was collected from 3279 adults above 15 years of age.(Urban and Rural settings) Lindi and Morogoro regions.To assess, through household questionnaires, the associations between selected predictors and individual drug uptake shortly after the implementation of MDA in two rural and two urban Districts in TanzaniaDrug uptake relied more on easily modifiable provider-related factors than on individual perceptions and practices in the target population.Motivation of drug distributors to visit all households (repeatedly when residents are absent) are likely to have considerable potential for increasing drug uptake.Coverage4. Madon et al, 2014 [45]/Tanzania/not statedQualitative study15 key informantsinterviews with Voluntary health workers (VHWs), village leaders and health officials.…”
Section: Resultsmentioning
confidence: 99%
“…In Sierra Leone and Mali, high MDA for LF coverage was attained in urban settings after having previously recorded low coverage by hiring of paid CDDs [22, 23, 37]. These studies established that the volunteer system of CDDs was ineffective in urban settings, especially in over-populated, rapidly urbanizing and mixed ethnic communities. Management of adverse/side effects Side effects were some of the major reasons why community members did not participate in MDA for LF [21, 38, 40]. Successful MDA programmes had well-established plans for any adverse effects during implementation [34, 36, 37, 3941].…”
Section: Resultsmentioning
confidence: 99%
“…In many instances it has been shown that irrespective of the reported coverage levels, large numbers of people being targeted either refuse to swallow them or they are not offered them in the first place (e.g. Ranganath, 2010;Roy et al, 2013;Muhumuza et al, 2013Muhumuza et al, , 2015Kisoka et al, 2014Kisoka et al, , 2016Tuhebwe et al, 2015). These points relate to a fourth broad area of concern: the role of drug distributors in mass treatment programmes.…”
Section: Introductionmentioning
confidence: 99%